Exploring identity in Korean diaspora fiction - Kang, Byoung Yoong (Asian studies, 2025)
This study examines the complex identity issues faced by Henry Park, the protagonist of Chang-Rae Lee’s novel Native Speaker, through the lens of Hannah Arendt’s con-cepts of the pariah and parvenu. By examining Henry’s experiences as a 1.5-generation Korean-American immigrant, this analysis elucidates the tensions between cultural as-similation and heritage preservation. The study describes Henry as a “Lesser Stranger”, a nuanced identity state situated between complete alienation and full assimilation. Fur-thermore, the analysis draws parallels with Frantz Fanon’s Black Skin, White Masks in or-der to gain further insight into Henry’s internal conflict and external societal pressures. In conclusion, this paper offers a comprehensive examination of the Korean-American expe-rience, contributing to broader discussions on diaspora, identity, and cultural integration.
Keywords: cultural conflict; diaspora experience; diasporna izkušnja; identiteta in asimilacija; identity and assimilation; Korean-American literature; korejsko-ameriška literatura; kulturni konflikt; pariah and parvenu; parij in parvenu